PROCEEDINGS OF CURED AND CRHONIC CONFERENCE - INTRODUCTION - Vittorio Mattioli (Journal of Cancer Rehabilitation)
The IX European Conference Cured & Chronic, held in Siracusa (Italy) on October 23, 2024, has entrusted distinguished worldwide speakers with the task of focusing on the main issues that arise during and beyond the cancer journey. Specifically, the articles in this Special Issue evaluate the impact of rehabilitation treatments on cancer survi- vors or those who have been cured.